Wątki Maryjne w katechezie parafialnej i przedsiewzięciach pastoralnych - Andrzej Kielian; Natalia Walkowiak (Colloquia Theologica Ottoniana, 2018)
The article presents Marian motives in parish catechesis and pastoral projects in Poland. The importance of the parish and the role of mariology in catechesis were depicted at first. Attention was paid to both the piety aspect and the teaching about Mary. The paper discusses the results of the survey in 26 selected Polish Catholic parishes on the forms of Marian devotion and the participation of children and young people in Marian services (like the rosary, Rorate Mass, pilgrimages to Marian shrines) as well as the Marian profile of parish groups especially for children and young people. The research has shown that parish groups gather only a small percentage of children and young people, while various forms of Marian devotion in parishes enjoy a higher turnout. The analysis has also stressed the importance of a proper preparation of parish communities leaders as far as the Marian aspect of their activity is concerned.